2004
DOI: 10.1051/rnd:2004065
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maturation culture period on the development of canine oocytes after in vitro maturation and fertilization

Abstract: -The objective of this study was to determine an optimum maturation period of canine oocytes for the development in vitro after in vitro fertilization (IVF). Canine oocytes larger than 110 micrometers in diameter, which were collected from ovaries at the follicular phase of the reproductive cycle, were cultured for each time (48, 72 and 96 h) in TCM 199 medium supplemented with 10% canine serum, fertilized, and then cultured in vitro for 8 days. Significantly more oocytes reached metaphase II (MII) in the 72-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 22 publications
4
36
1
Order By: Relevance
“…When recovered directly from ovarian follicles and incubated, some oocytes advance to the MII stage by as early as 24 h of culture (Robertson et al, 1992;Yamada et al, 1992Yamada et al, , 1993Nickson et al, 1993;Saint-Dizier et al, 2004). Increasing the culture period to 48 h has resulted in more oocytes completing nuclear maturation, but with few exceptions (Otoi et al, 2004;de los Reyes et al, 2005) a more protracted incubation (beyond 48 hours) fails to increase the total number of MII oocytes produced (Robertson et al, 1992;Yamada et al, 1992Yamada et al, , 1993Nickson et al, 1993;Songsasen et al, 2003b;Saint-Dizier et al, 2004) and even increases oocyte degeneration (Nickson et al, 1993;Luvoni et al, 2003;Songsasen et al, 2003b). Thus, the optimal interval for IVM of dog oocytes appears to be 48 h, which also correlates to best embryonic development after IVF (Otoi et al, 2004).…”
Section: Culture Intervalmentioning
confidence: 99%
“…When recovered directly from ovarian follicles and incubated, some oocytes advance to the MII stage by as early as 24 h of culture (Robertson et al, 1992;Yamada et al, 1992Yamada et al, , 1993Nickson et al, 1993;Saint-Dizier et al, 2004). Increasing the culture period to 48 h has resulted in more oocytes completing nuclear maturation, but with few exceptions (Otoi et al, 2004;de los Reyes et al, 2005) a more protracted incubation (beyond 48 hours) fails to increase the total number of MII oocytes produced (Robertson et al, 1992;Yamada et al, 1992Yamada et al, , 1993Nickson et al, 1993;Songsasen et al, 2003b;Saint-Dizier et al, 2004) and even increases oocyte degeneration (Nickson et al, 1993;Luvoni et al, 2003;Songsasen et al, 2003b). Thus, the optimal interval for IVM of dog oocytes appears to be 48 h, which also correlates to best embryonic development after IVF (Otoi et al, 2004).…”
Section: Culture Intervalmentioning
confidence: 99%
“…For example, the age of the donor bitch [3], oocyte diameter [4,5], protein [6][7][8][9][10] and hormonal supplementation of maturation media [11][12][13][14][15][16] have all been examined. However, the proportion of MII oocytes remains low (0-43.4%) [9,[15][16][17][18][19][20], and a number of essential issues have yet to be resolved.One of these issues is the optimal culture period for IVM of canine oocytes. When oocytes are recovered directly from ovarian follicles and cultured in vitro, some progress to the MII stage after as little as 24 h of culture [17,21,22], and de los Reyes et al [15] demonstrated that some of oocytes reach the MII stage after 96 h of culture.…”
mentioning
confidence: 99%
“…When oocytes are recovered directly from ovarian follicles and cultured in vitro, some progress to the MII stage after as little as 24 h of culture [17,21,22], and de los Reyes et al [15] demonstrated that some of oocytes reach the MII stage after 96 h of culture. On the other hand, some reports suggest that the optimal culture time for IVM may be 72 h [9,22], while Otoi et al [19] report that the optimal interval for IVM of canine oocytes appears to be 48 h, which also correlates with the best embryonic development after in vitro fertilization, though more oocytes progress to the MII stage after 96 h of culture. One of the reasons for the difficulty in determining the optimal culture interval is that the presence of a large amount of lipid droplets in the cytoplasm significantly hinders chromatin observation.…”
mentioning
confidence: 99%
“…Ovaries were collected from 26 domestic cats (crossbred of different breeds; ages 1-3 years) by routine ovariohysterectomy following anesthesia at different local veterinary clinics and maintained in Phosphate Buffered Saline (PBS) at 35°C for 3 h. The ovaries were sliced with a scalpel blade and rinsed in washing medium [30] at room temperature in order to obtain cumulus oocytes complexes (COCs). COCs were washed three times with Ham's F-10 medium [31] .…”
Section: Collection Of Ovaries and Recovery Of Oocytesmentioning
confidence: 99%